Temperature changes in contact lenses in connection with radiation from welding arcs - Lövsund, Per; Nilsson, Sven Erik G.; Lindh, Hans; Öberg, P. Åke (Scandinavian Journal of Work, Environment & Health, 1979)
Because of reports of risks associated with the use of contact lenses during exposure to welding arcs, the temperature changes in soft contact lenses were recorded in connection with certain types of welding [manual metal arc (MMA) welding, tungsten inert-gas (TIG) welding, and metal inert-gas (MIG) welding], both with free-hanging lenses and lenses applied to the eyes of anesthetized rabbits. A great increase in temperature was noted, especially with MMA welding. At a distance of 0.4 m the temperature of a lens on a rabbit eye rose from about 35 to 50°C within 6 min, whereas the air temperature only increased from 23 to 30°C. The increase was the greatest at the beginning of the welding period. Most of the lenses completely dried out during the experiment, and there would seem to be a potential risk that the lens would adhere to the cornea. One safety glass screen (DIN 10 A) proved effective in preventing the rise in temperature in contact lenses during MMA welding. Even though it is impossible to direct the eyes at the arc for a prolonged period of time, the use of contact lenses in connection with at least certain types of welding is not to be recommended without the use of a suitable safety glass screen (or safety glasses). With regard to the large number of particles in the welding environment, also a risk factor for contact lens wearers, it is doubtful whether even safety glasses or screens are satisfactory unless they fit closely.
Keywords: contact lense; corneal damage; occupational safety; radiation; radiation hazard; soft contact lense; temperature; temperature change; welding; welding arc; worker safety